2006
DOI: 10.1590/s0103-50532006000300019
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological responses of eucalyptus brown looper Thyrinteina arnobia to essential oils of seven Eucalyptus species

Abstract: A lagarta-parda, Thyrinteina arnobia, causa grandes prejuízos à cultura do eucalipto, destacando-se como o principal lepidóptero desfolhador; portanto, medidas alternativas de controle são necessárias. Neste trabalho foi avaliada, pela técnica de eletroantenografia (EAG), a interação dos voláteis dos óleos essenciais de sete espécies de Eucalyptus, frente às antenas de fêmeas e de machos de T. arnobia. Foram também identificados 28 compostos voláteis bioativos contidos no óleo essencial de E. grandis, utilizan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Our findings are similar to those from Tsiri et al [21] and Cimanga et al [16], who revealed that the major components of Eucalyptus oils was 1,8-cineole. The chemical profiles of a variety of other Eucalyptus species have been published [22,23], and are comparable to our results. Nevertheless, Singh et al (22) extracted the leaf oil of E. urophylla from India, with p-cymene (75.0 %), α-pinene (7.0 %), and α-terpinene (4.0 %) being the main compounds.…”
supporting
confidence: 89%
“…Our findings are similar to those from Tsiri et al [21] and Cimanga et al [16], who revealed that the major components of Eucalyptus oils was 1,8-cineole. The chemical profiles of a variety of other Eucalyptus species have been published [22,23], and are comparable to our results. Nevertheless, Singh et al (22) extracted the leaf oil of E. urophylla from India, with p-cymene (75.0 %), α-pinene (7.0 %), and α-terpinene (4.0 %) being the main compounds.…”
supporting
confidence: 89%
“…1,8-cineole which is a principal component of most Eucalyptus essential oils was of very low percentage in in the leaf essential oil of E. maculata grown in Nigeria (Table 1). This result is similar to what was obtained from the leaf essential oil of the plant from Brazil, Iran and Tunisia [30][31][32]. Most of the secondary metabolites present in this essential oil were reported to have good pharmacological properties [33][34][35][36].…”
Section: Chemical Composition Of the Leaf Essential Oilsupporting
confidence: 85%
“…In general, it affords good extraction yields of EOs as observed in the studies from plants cultivated in India [54] and in Benin [99] (4.8% and 4.6% yields, respectively). Lower oil yielding species were found, however, in India (0.6%) [26], in São Paulo State, Brazil (0.66%) [70,71] and Colombia (0.70%) [102]. Typically, citronellal is the major constituent in E. citriodora EOs.…”
Section: Eucalyptus Citriodoramentioning
confidence: 98%
“…For most E. camaldulensis EOs, 1,8-cineole is the major constituent. This oxygenated monoterpene has been found in quantities superior to 50% in EOs produced by plants cultivated in Egypt (60.3%) [63], the Democratic Republic of the Congo (58.9%) [53], Nigeria (70.4%) [67], Brazil (52.8%) [70,71] and Iran (74.7%) [69]. Plants cultivated in Kenya [78], Northern Cyprus [64] and Argentina [75,76] …”
Section: Eucalyptus Camaldulensismentioning
confidence: 99%
See 1 more Smart Citation